Suicidal rare craniocerebral injury and its complications - Pradeep Bharti Gupta; Sona B. Kaushal; Uday Gupta (Indian Journal of Neurosurgery)
The authors here describe a rare cranio-cerebral injury, which occurred due to a self-inflicted suicidal attempt by the patient, who hammered an 8 cm long nail into his skull. This patient was a known case of schizophrenia. The nail entered in the region of the left parafalx area and reached almost up to the base of skull of the patient. This nail was removed by a mid-line craniotomy. Approximately six months later, the patient presented with the symptoms of raised intra cranial pressure and right hemi paresis. Repeat computed tomography scan showed a large brain abscess at the site of the previous surgery and the patient was re-explored through the previous incision; the abscess was drained and the wall was excised. The patient then made a good recovery.